Multi-element cemented filling paste and preparation method thereof
Patent Information
- Application Number
- CN202611239952.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]综上所述,现有电石渣-赤泥协同利用技术多集中于软土固化、免烧砖、地聚物等功能材料领域,尚未出现专门针对矿山充填场景、兼顾早期强度、流动性能、抗泌水性及重金属主动固定功能的多元胶结充填膏体
1)本发明首次构建面向矿山充填的“电石渣-赤泥-煅烧煤矸石-硅灰”四元协同激发体系,通过赤泥的高碱性环境有效激发电石渣及煅烧煤矸石的火山灰活性,电石渣提供丰富钙源,促进C-S-H凝胶生成,硅灰通过微集料填充与火山灰效应提升体系致密性;四元组分的协同作用使材料兼具优异的早期强度与长期强度,完全满足矿山充填对早期支撑能力和长期稳定性的要求,填补了电石渣-赤泥协同体系在矿山充填专用材料领域的技术空白;
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the fields of solid waste resource utilization and mine environmental remediation, and in particular to a multi-component cemented filling paste and its preparation method. Background Technology
[0002] With the acceleration of industrialization, the generation and accumulation of large quantities of industrial solid waste have become a severe challenge restricting sustainable economic and social development and threatening ecological and environmental security. Among various industrial solid wastes, coal gangue, carbide slag, and red mud have huge annual outputs, low comprehensive utilization rates, and prominent environmental risks. Long-term accumulation of coal gangue can easily lead to spontaneous combustion and dust, and its potential heavy metal leaching risk poses a threat to the soil and water environment; carbide slag has poor stability and low early activity, and large-scale accumulation occupies land resources; red mud is highly alkaline (pH>12), and improper treatment can easily lead to soil salinization. At the same time, the goaf areas formed by mining urgently need safe, economical, and environmentally friendly filling materials for treatment to prevent geological disasters such as surface subsidence.
[0003] Currently, the technical solutions for the co-utilization of carbide slag and red mud mainly focus on the following aspects, but all of them have limitations to varying degrees: 1) Soft Soil Stabilization and Non-fired Brick Preparation Technology: Existing research attempts to synergistically use carbide slag and red mud for soft soil stabilization or non-fired brick preparation. For example, Chinese invention patent application CN117326826A describes a soft soil stabilizing agent for the complete solid waste harmlessness treatment, formulated from phosphogypsum, red mud, carbide slag, and mineral powder. Another example is Chinese invention patent application CN113105172A, which describes a preparation process for non-fired bricks using fly ash from municipal solid waste incineration synergistically with red mud and carbide slag. However, these technologies mainly target the field of soft soil reinforcement or building materials, without addressing the design of paste materials for mine backfilling scenarios, and lack systematic optimization of the material's early strength, flowability, and pumpability. 2) Geopolymer and Cementitious Material Technology: Some research focuses on the development of calcium carbide slag-red mud geopolymers. For example, Chinese invention patent application CN112250333A describes a bottom ash / water-rich calcium carbide slag / red mud geopolymer and its preparation method, in which the bottom ash and water-rich calcium carbide slag are added in amounts of 60%-85%, and 5%-20% alkali activator is required. Another example is Chinese invention patent application CN111574078A, which describes a method for activating fly ash-red mud geopolymers using calcium carbide slag, but its components are mainly fly ash, red mud, and calcium carbide slag, requiring the addition of sand as aggregate. While these solutions achieve solid waste resource utilization, they do not solve the problems of synergistic activation and active heavy metal capture among multiple solid waste sources, and they do not pay sufficient attention to the anti-bleeding properties and long-term stability required for mine backfilling. 3) Functional Building Materials Technology: In recent years, the red mud-carbide slag synergistic system has also been explored in the field of functional building materials. For example, Chinese invention patent application CN112707663A describes a method for preparing red mud core-shell structured fine aggregate, with the core material made of red mud and carbide slag to prepare functional components; Chinese invention patent application CN111847995A describes a red mud-based solid waste permeable concrete and its preparation method, with raw materials including red mud, blast furnace slag and carbide slag. These technologies focus on the specific functions of concrete aggregates or permeable materials, do not involve the active chemical capture mechanism of heavy metals, and have significantly different requirements for the early strength and workability of materials compared to mine backfilling. 4) Current Status of Heavy Metal Stabilization Technology: Existing filling materials primarily employ a "passive" process for heavy metal stabilization, relying on physical sealing by gels or surface adsorption by adsorbents. This mechanism has limited capacity, and there is a risk of pollutant re-migration when the material structure is damaged or environmental conditions change. There is a lack of "active chemical trapping" capabilities that can actively and directionally convert heavy metal ions into stable mineral phases.
[0004] In summary, existing technologies for the co-utilization of carbide slag and red mud are mostly concentrated in the fields of functional materials such as soft soil solidification, non-fired bricks, and geopolymers. There is no multi-component cemented filling paste specifically designed for mine backfilling scenarios that takes into account early strength, flowability, water resistance, and active fixation of heavy metals.
[0005] Therefore, it is of great significance to provide a low-cost, multi-element cemented backfill paste that can simultaneously and efficiently utilize bulk solid wastes from multiple sources such as coal gangue, carbide slag, and red mud, while also possessing excellent early mechanical properties, good workability, and the ability to actively stabilize heavy metals over a long period. Summary of the Invention
[0006] To address the aforementioned technical problems, the present invention aims to provide a multi-component cementitious filling paste and its preparation method.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a multi-component cementitious filling paste, prepared from raw materials comprising the following parts by weight: 30-45 parts of coal gangue, 15-25 parts of calcium carbide slag 10-20 parts red mud 5-15 parts silica fume 5-12 parts water glass 3-8 parts of heavy metal targeted trapping agent 1-4 parts of reaction trigger modifier, 15-25 parts water.
[0008] Furthermore, the heavy metal targeted trapping agent is at least two of phosphates, sulfides, barium salts, and ferrous salts.
[0009] Furthermore, the reaction triggering regulator is a slow-release alkaline substance and / or a pH buffer; The sustained-release alkaline substance includes coated calcium oxide and / or coated magnesium oxide; The pH buffer includes one or more of citrate, tartrate, phosphate, and bicarbonate.
[0010] Furthermore, the particle size of the coal gangue is ≤45μm; The calcium carbide slag is the waste residue generated during the process of producing chemical products by calcium carbide hydrolysis, and the particle size of the calcium carbide slag is ≤30μm; The red mud is Bayer process red mud or sintering process red mud, and the particle size of the red mud is ≤30μm; The silica fume is micro silica powder, with a SiO2 content ≥90% and a particle size of 0.1~0.3μm.
[0011] Furthermore, the modulus of the water glass is 1.5 to 2.5, and the solid content is 35 to 45%.
[0012] The present invention also provides a method for preparing the aforementioned multi-component cementitious filling paste, comprising the following steps: 1) Calcine and activate coal gangue to obtain calcined coal gangue; 2) The calcined coal gangue, carbide slag, red mud and silica fume are dry-mixed to obtain a dry mixture; 3) Mix water glass, heavy metal directional trapping agent, reaction triggering regulator and water to obtain a liquid mixture; 4) Mix the liquid mixture and the dry mixture to obtain a multi-component cementitious filling paste; Steps 2) and 3) are not in any particular order.
[0013] Furthermore, in step 1), the calcination activation temperature is 800~950℃, and the calcination activation time is 1~3h.
[0014] Furthermore, in step 2), the dry mixing speed is 60~120 rpm, and the dry mixing time is 3~6 min.
[0015] Furthermore, in step 3), the mixing speed is 200~400 rpm and the mixing time is 2~4 min.
[0016] Furthermore, in step 4), the mixing process is as follows: first, low-speed mixing is performed at a speed of 80~120 r / min for 1~2 min, and then high-speed mixing is performed at a speed of 120~180 r / min for 3~5 min.
[0017] The beneficial effects of this invention are: 1) This invention is the first to construct a quaternary synergistic activation system for mine backfilling, consisting of "carbide slag-red mud-calcined coal gangue-silica fume". The highly alkaline environment of red mud effectively activates the pozzolanic activity of carbide slag and calcined coal gangue. Carbide slag provides a rich calcium source and promotes CSH gel formation. Silica fume enhances the system's density through micro-aggregate filling and pozzolanic effect. The synergistic effect of the quaternary components gives the material both excellent early strength and long-term strength, fully meeting the requirements of mine backfilling for early support capacity and long-term stability, filling the technological gap in the field of carbide slag-red mud synergistic system for mine backfilling materials. 2) This invention is the first to employ an active chemical capture mechanism for heavy metals, overcoming the limitations of traditional passive storage. By introducing a heavy metal-directed capture agent and a reaction triggering regulator, the system induces Pb in situ during hydration. 2+ Cd 2+ Cr 2+ Heavy metal ions are converted into thermodynamically stable insoluble mineral phases (such as lead phosphate, cadmium sulfide, barium chromate, etc.). The reaction trigger regulator ensures that the mineralization reaction is completed under optimal conditions by precisely controlling the pH window and reaction rate. This achieves a technological leap from passive storage to active capture, significantly improving the long-term safety of materials in harsh environments such as acidic mine drainage. 3) This invention optimizes the particle size distribution of raw materials and uses a step-by-step mixing process of dry mixing followed by liquid mixing to make the paste structure dense and uniform, with good fluidity and anti-bleeding properties, excellent pumpability, and suitable for long-distance pipeline transportation and continuous construction in underground mines. It solves the engineering problem of difficulty in ensuring the working performance of bulk solid waste in mine backfilling applications. 4) This invention uses bulk industrial solid waste such as coal gangue, carbide slag, and red mud as the main raw materials, and uses small amounts of additives such as silica fume and water glass. The raw materials are widely available and inexpensive. The preparation process does not require special and complicated equipment, only conventional mixing and stirring devices. The process is simple and controllable, and it is easy to realize industrial production in mines or centralized solid waste treatment sites. It provides a practical and feasible technical path for the resource utilization of multi-source solid waste and the environmental management of mines. Detailed Implementation
[0018] This invention provides a multi-component cementitious filling paste, prepared from raw materials comprising the following parts by weight: 30-45 parts of coal gangue, 15-25 parts of calcium carbide slag 10-20 parts red mud 5-15 parts silica fume 5-12 parts water glass 3-8 parts of heavy metal targeted trapping agent 1-4 parts of reaction trigger modifier, 15-25 parts water.
[0019] In this invention, the content of coal gangue is preferably 32-43 parts by mass, and more preferably 35-40 parts by mass.
[0020] In this invention, the particle size of the coal gangue is ≤45μm, preferably ≤43μm, and more preferably ≤40μm.
[0021] In this invention, the content of the carbide slag is preferably 17 to 23 parts by mass, and more preferably 19 to 21 parts by mass.
[0022] In this invention, the calcium carbide slag is the waste residue generated during the process of producing chemical products by calcium carbide hydrolysis. The particle size of the calcium carbide slag is ≤30μm, preferably ≤28μm, and more preferably ≤25μm.
[0023] In this invention, the content of the red mud is preferably 12 to 18 parts by mass, and more preferably 14 to 16 parts by mass.
[0024] In this invention, the red mud is Bayer process red mud or sintering process red mud, and the particle size of the red mud is ≤30μm, preferably ≤27μm, and more preferably ≤25μm.
[0025] In this invention, the content of silica fume is preferably 6 to 13 parts by weight, and more preferably 8 to 12 parts by weight.
[0026] In this invention, the silica fume is micro silica powder, and the SiO2 content in the silica fume is ≥90%, preferably ≥91%, and more preferably ≥92%; the particle size of the silica fume is 0.1~0.3μm, preferably 0.15~0.25μm, and more preferably 0.2μm.
[0027] In this invention, the content of water glass is preferably 6 to 11 parts by weight, and more preferably 7 to 10 parts by weight.
[0028] In this invention, the modulus of the water glass is 1.5 to 2.5, preferably 1.6 to 2.4, and more preferably 1.7 to 2.3; the solid content is 35 to 45%, preferably 37 to 43%, and more preferably 40%.
[0029] In this invention, the content of the heavy metal directional trapping agent is preferably 4 to 7 parts by weight, and more preferably 5 to 6 parts by weight.
[0030] In this invention, the heavy metal directional trapping agent is at least two of phosphate, sulfide, barium salt and ferrous salt, preferably at least two of phosphate, barium salt and ferrous salt, and more preferably phosphate and ferrous salt.
[0031] In this invention, the content of the reaction triggering regulator is preferably 1.5 to 3.5 parts by mass, and more preferably 2 to 3 parts by mass.
[0032] In this invention, the reaction triggering regulator is a slow-release alkaline substance and / or a pH buffer, preferably a mixture of a slow-release alkaline substance and a pH buffer.
[0033] In this invention, the slow-release alkaline substance includes coated calcium oxide and / or coated magnesium oxide, preferably coated calcium oxide; The pH buffer comprises one or more of citrate, tartrate, phosphate and bicarbonate, preferably one or more of citrate, tartrate and phosphate, and more preferably citrate and / or tartrate.
[0034] In this invention, the water content is preferably 17 to 23 parts by mass, and more preferably 20 parts by mass.
[0035] The present invention also provides a method for preparing the aforementioned multi-component cementitious filling paste, comprising the following steps: 1) Calcine and activate coal gangue to obtain calcined coal gangue; 2) The calcined coal gangue, carbide slag, red mud and silica fume are dry-mixed to obtain a dry mixture; 3) Mix water glass, heavy metal directional trapping agent, reaction triggering regulator and water to obtain a liquid mixture; 4) Mix the liquid mixture and the dry mixture to obtain a multi-component cementitious filling paste; Steps 2) and 3) are not in any particular order.
[0036] In this invention, in step 1), the calcination activation temperature is 800~950℃, preferably 820~930℃, and more preferably 850~900℃; the calcination activation time is 1~3h, preferably 1.5~2.5h, and more preferably 2h.
[0037] In this invention, in step 2), the dry mixing speed is 60~120 rpm, preferably 70~110 rpm, and more preferably 80~100 rpm; the dry mixing time is 3~6 min, preferably 3.5~5.5 min, and more preferably 4~5 min.
[0038] In this invention, if the dry mixing speed is too low, the mixing speed will be insufficient, especially for micron-sized silica fume (which is very easy to agglomerate) and high-density calcium carbide slag powder, which are prone to stratification or clumping, making it difficult to achieve a uniform state within a reasonable time (3-6 minutes). If the speed is too high, the ultrafine silica fume particles will agglomerate more tightly due to factors such as static electricity, which is not conducive to their uniform distribution in the dry material. At the same time, it will cause serious dust flying, which not only pollutes the environment and harms health, but also leads to the loss of key components in the formula and affects the accuracy of the final paste composition.
[0039] In this invention, in step 3), the rotation speed of the liquid mixing is 200~400 rpm, preferably 220~380 rpm, and more preferably 250~350 rpm; the liquid mixing time is 2~4 min, preferably 2.5~3.5 min, and more preferably 3 min.
[0040] In this invention, in step 4), the mixing process is to first mix at a low speed of 80~120 r / min for 1~2 min, and then mix at a high speed of 120~180 r / min for 3~5 min.
[0041] Preferably, the mixing process involves first mixing at a low speed of 85-115 r / min for 1.2-1.8 min, and then mixing at a high speed of 130-170 r / min for 3.2-4.7 min.
[0042] More preferably, the mixing process involves first mixing at a low speed of 90-110 r / min for 1.4-1.6 min, and then mixing at a high speed of 140-160 r / min for 3.5-4.5 min.
[0043] In this invention, the mixing process is divided into two stages. The first stage is low-speed mixing, which aims to initially wet all powder particles with liquid. The second stage is high-speed mixing, which aims to break up particle agglomeration and obtain a multi-component cementitious filling paste with good flowability and uniformity without lumps.
[0044] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0045] Example 1
[0046] After crushing 35 parts of coal gangue, it was placed in a muffle furnace and calcined at 850℃ for 2 hours. After cooling, it was ground to a particle size of 40μm to obtain calcined coal gangue powder. Calcined coal gangue powder, 20 parts of calcium carbide slag powder with a particle size of 25 μm, 15 parts of Bayer red mud powder with a particle size of 25 μm and 10 parts of silica fume with a particle size of 0.2 μm (the silica fume contains 92% SiO2) were dry mixed at 80 rpm for 4 minutes to obtain a uniform dry mix. Eight parts of water glass with a modulus of 2.0 and a solid content of 40%, five parts of heavy metal directional trapping agent (the heavy metal directional trapping agent is a mixture of calcium dihydrogen phosphate and ferrous sulfate in a mass ratio of 3:1), two parts of coated calcium oxide microspheres and 20 parts of water were mixed at 300 rpm for 3 minutes to obtain a homogeneous liquid mixture. The liquid mixture is slowly added to the dry mixture. First, it is mixed at a low speed of 100 r / min for 1.5 minutes, and then at a high speed of 150 r / min for 4 minutes to finally obtain the multi-component cementitious filling paste.
[0047] Example 2
[0048] Forty parts of coal gangue were crushed and placed in a muffle furnace and calcined at 900℃ for 1.5h. After cooling, they were ground to a particle size of 38μm to obtain calcined coal gangue powder. Calcined coal gangue powder, 18 parts of calcium carbide slag powder with a particle size of 28 μm, 12 parts of sintered red mud powder with a particle size of 27 μm, and 8 parts of silica fume with a particle size of 0.25 μm (the silica fume contains 91% SiO2) were dry-mixed at 90 rpm for 5 minutes to obtain a uniform dry mix. Ten parts of water glass with a modulus of 1.8 and a solid content of 38%, six parts of heavy metal directional trapping agent (the heavy metal directional trapping agent is a mixture of disodium hydrogen phosphate and barium chloride in a mass ratio of 2:1), 1.5 parts of sodium citrate and 18 parts of water were mixed at 250 rpm for 3.5 minutes to obtain a homogeneous liquid mixture. The liquid mixture is slowly added to the dry mixture. First, it is mixed at a low speed of 110 r / min for 1 minute, and then at a high speed of 160 r / min for 3.5 minutes to finally obtain the multi-component cementitious filling paste.
[0049] Example 3
[0050] After crushing 32 portions of coal gangue, it was placed in a muffle furnace and calcined at 820℃ for 2.5 hours. After cooling, it was ground to a particle size of 42μm to obtain calcined coal gangue powder. Calcined coal gangue powder, 22 parts of calcium carbide slag powder with a particle size of 22 μm, 18 parts of Bayer red mud powder with a particle size of 23 μm, and 12 parts of silica fume with a particle size of 0.15 μm (the silica fume contains 93% SiO2) were dry-mixed at 100 rpm for 3.5 minutes to obtain a uniform dry mix. Six parts of water glass with a modulus of 2.2 and a solid content of 42%, four parts of heavy metal directional trapping agent (the heavy metal directional trapping agent is a mixture of sodium sulfide and ferrous sulfate in a mass ratio of 1:1), three parts of reaction triggering regulator made by mixing coated calcium oxide microspheres and potassium sodium tartrate in a mass ratio of 2:1, and 22 parts of water were mixed at 350 rpm for 2.5 minutes to obtain a homogeneous liquid mixture. The liquid mixture is slowly added to the dry mixture. First, it is mixed at a low speed of 90 r / min for 2 minutes, and then at a high speed of 140 r / min for 4.5 minutes to finally obtain the multi-component cementitious filling paste.
[0051] Example 4
[0052] After crushing 38 portions of coal gangue, it was placed in a muffle furnace and calcined at 880℃ for 2 hours. After cooling, it was ground to a particle size of 35μm to obtain calcined coal gangue powder. Calcined coal gangue powder, 17 parts of calcium carbide slag powder with a particle size of 26 μm, 14 parts of Bayer red mud powder with a particle size of 24 μm, and 9 parts of silica fume with a particle size of 0.22 μm (the silica fume contains 92.5% SiO2) were dry-mixed at 85 rpm for 4.5 minutes to obtain a uniform dry mix. Nine parts of water glass with a modulus of 2.0 and a solid content of 39%, 5.5 parts of heavy metal directional trapping agent (the heavy metal directional trapping agent is a mixture of calcium dihydrogen phosphate, ferrous sulfate and barium chloride in a mass ratio of 2:1:1), 2.5 parts of reaction triggering regulator made by mixing coated magnesium oxide microspheres and potassium dihydrogen phosphate in a mass ratio of 3:1, and 19 parts of water were mixed at 280 rpm for 3 minutes to obtain a homogeneous liquid mixture. The liquid mixture is slowly added to the dry mixture. First, it is mixed at a low speed of 105 r / min for 1.2 minutes, and then at a high speed of 155 r / min for 3.8 minutes to finally obtain the multi-component cementitious filling paste.
[0053] Comparative Example 1
[0054] The difference between this example and Example 1 is that no red mud was added in Comparative Example 1.
[0055] Comparative Example 2
[0056] Compared with Example 1, the difference is that Comparative Example 2 uses a single heavy metal targeted trapping agent, which is 5 parts of calcium dihydrogen phosphate and does not contain ferrous sulfate.
[0057] Comparative Example 3
[0058] Compared with Example 1, the difference is that no reaction triggering regulator was added in Comparative Example 3, and the amount of water was 22 parts.
[0059] Comparative Example 4
[0060] Compared with Example 1, the difference is that Comparative Example 4 uses a traditional cement-based filling material system. 30 parts of P.O42.5 cement, 20 parts of raw coal gangue coarse aggregate with a particle size of 5-10 mm, 25 parts of raw coal gangue fine aggregate with a particle size of 5 mm and 25 parts of water are stirred at a speed of 150 r / min for 5 minutes to obtain a paste.
[0061] The performance of the ointments prepared in Examples 1-4 and Comparative Examples 1-4 was tested using the following methods: Compressive strength test: Refer to GB / T 17671-2021 Cement Mortar Strength Test Method, prepare 40mm×40mm×160mm specimens, cure under standard conditions (temperature 20±1℃, relative humidity ≥95%) to the specified age (3d, 7d, 28d), and use a universal testing machine to determine the compressive strength; Slump: The slump was measured using a slump cone, referring to GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures". Flowability: The bouncy table method was adopted, referring to "GB / T 2419-2005 Test Method for Flowability of Cement Mortar"; Bleeding rate: Refer to "JGJ / T 70-2009 Test Methods for Basic Performance of Building Mortar" to determine the amount of water bled after standing. Leaching toxicity test: The leaching concentrations of heavy metals such as Pb, Cd, and Cr were determined in accordance with the "HJ / T 300-2007 Solid Waste Leaching Toxicity Leaching Method Acetic Acid Buffer Solution Method" and "GB 5085.3-2007 Hazardous Waste Identification Standard Leaching Toxicity Identification". Setting time: Refer to GB / T 1346-2011 Standard Cement Consistency Water Requirement, Setting Time and Soundness Test Method.
[0062] The test results are shown in Table 1.
[0063] Table 1 Performance test results of Examples 1-4 and Comparative Examples 1-4
[0064] As shown in Table 1, the 3-day compressive strength of Examples 1-4 of the present invention reaches 3.8-4.5 MPa, and the 28-day compressive strength reaches 14.2-16.8 MPa, both significantly higher than that of the traditional cement-based system in Comparative Example 4 (where the 28-day compressive strength is only 11.8 MPa). This indicates that the quaternary composite system of "carbide slag-red mud-calcined coal gangue-silica fume" constructed in the present invention has superior cementitious activity and strength development ability. The slump and fluidity of the examples are better than those of the comparative examples, and the bleeding rate is low, at 1. The concentration of Pb, Cd, and Cr in the samples was 0-1.4%, indicating that the paste had good fluidity and was not prone to segregation, and possessed good pumpability and applicability for downhole transportation. In the examples, the leaching concentrations of Pb, Cd, and Cr were much lower than those in Comparative Example 1 (without red mud), Comparative Example 2 (single trapping agent), and Comparative Example 4 (traditional cement system). In particular, the leaching concentration of Pb was only 0.07-0.12 mg / L, indicating that the alkaline activation of red mud and the synergistic effect of the composite heavy metal directional trapping agent can effectively transform heavy metals into stable mineral phases and achieve long-term stabilization. The leaching toxicity of the red mud in Comparative Example 1 was significantly increased, indicating that the red mud not only provides an alkaline environment to stimulate gelation activity, but also participates in the chemical fixation of heavy metals. The heavy metal fixation effect of Comparative Example 2 (single trapping agent) was significantly reduced, proving that the combination of multiple trapping agents can exert a synergistic trapping advantage against different heavy metal ions. Although the early strength of Comparative Example 3 was slightly higher, the bleeding rate increased and the heavy metal fixation effect weakened, indicating that the reaction triggering regulator can optimize the reaction process and microenvironment, and improve the overall performance. The initial setting time and final setting time of the examples were between those of Comparative Example 3 (no regulator, setting too fast) and Comparative Example 4 (traditional cement, setting too slowly), indicating that the system has suitable setting regulation, which is convenient for on-site mixing and grouting construction.
[0065] As can be seen from the above embodiments, the present invention provides a multi-component cemented filling paste and its preparation method, which is prepared from the following raw materials in parts by weight: 30-45 parts coal gangue, 15-25 parts calcium carbide slag, 10-20 parts red mud, 5-15 parts silica fume, 5-12 parts water glass, 3-8 parts heavy metal directional trapping agent, 1-4 parts reaction triggering regulator, and 15-25 parts water. The present invention constructs a quaternary composite system of calcium carbide slag-red mud-calcined coal gangue-silica fume, and the prepared multi-component cemented filling paste exhibits excellent early strength, long-term strength, flow properties, and anti-bleeding properties. Furthermore, it has a significant chemical fixation effect on heavy metals such as Pb, Cd, and Cr, with leaching concentrations far below the national standard limits.
[0066] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A multi-component cementitious filling paste, characterized in that, It is prepared from raw materials comprising the following parts by weight: 30-45 parts of coal gangue, 15-25 parts of calcium carbide slag 10-20 parts red mud 5-15 parts silica fume 5-12 parts water glass 3-8 parts of heavy metal targeted trapping agent 1-4 parts of reaction trigger modifier, 15-25 parts water.
2. The multi-component cementitious filling paste according to claim 1, characterized in that, The heavy metal targeted trapping agent is at least two of phosphates, sulfides, barium salts, and ferrous salts.
3. The multi-component cementitious filling paste according to claim 2, characterized in that, The reaction triggering regulator is a slow-release alkaline substance and / or a pH buffer; The sustained-release alkaline substance includes coated calcium oxide and / or coated magnesium oxide; The pH buffer includes one or more of citrate, tartrate, phosphate, and bicarbonate.
4. The multi-component cementitious filling paste according to claim 2 or 3, characterized in that, The particle size of the coal gangue is ≤45μm; The calcium carbide slag is the waste residue generated during the process of producing chemical products by calcium carbide hydrolysis, and the particle size of the calcium carbide slag is ≤30μm; The red mud is Bayer process red mud or sintering process red mud, and the particle size of the red mud is ≤30μm; The silica fume is micro silica powder, with a SiO2 content ≥90% and a particle size of 0.1~0.3μm.
5. The multi-component cementitious filling paste according to claim 4, characterized in that, The water glass has a modulus of 1.5 to 2.5 and a solid content of 35 to 45%.
6. A method for preparing the multi-component cementitious filling paste according to any one of claims 1 to 5, characterized in that, Includes the following steps: 1) Calcine and activate coal gangue to obtain calcined coal gangue; 2) The calcined coal gangue, carbide slag, red mud and silica fume are dry-mixed to obtain a dry mixture; 3) Mix water glass, heavy metal directional trapping agent, reaction triggering regulator and water to obtain a liquid mixture; 4) Mix the liquid mixture and the dry mixture to obtain a multi-component cementitious filling paste; Steps 2) and 3) are not in any particular order.
7. The method for preparing the multi-component cementitious filling paste according to claim 6, characterized in that, In step 1), the calcination activation temperature is 800~950℃, and the calcination activation time is 1~3h.
8. The method for preparing the multi-component cementitious filling paste according to claim 7, characterized in that, In step 2), the dry mixing speed is 60~120 rpm and the dry mixing time is 3~6 min.
9. The method for preparing the multi-component cementitious filling paste according to claim 7 or 8, characterized in that, In step 3), the mixing speed is 200~400 rpm and the mixing time is 2~4 min.
10. The method for preparing the multi-component cementitious filling paste according to claim 9, characterized in that, In step 4), the mixing process is as follows: first, low-speed mixing is performed at a speed of 80~120 r / min for 1~2 min, and then high-speed mixing is performed at a speed of 120~180 r / min for 3~5 min.
Citation Information
Patent Citations
Fly ash-red mud based geopolymer excited by carbide slag and preparation method thereof
CN111574078A
Red mud-based solid waste pervious concrete as well as preparation method and application thereof
CN111847995A
Furnace bottom slag / water-rich carbide slag / red mud geopolymer and preparation method thereof
CN112250333A
Preparation method of red mud core-shell structure fine aggregate
CN112707663A
Heavy metal curing baking-free brick utilizing industrial solid waste and household garbage fly ash
CN113105172A